Corporate Social Responsibility (CSR): Models and Theories in Stakeholder Dialogue - O’Riordan, Linda (Journal of business ethics, 2008)
The pharmaceutical sector, an industry already facing stiff challenges in the form of intensified competition and strategic consolidation, has increasingly become subject to a range of pressures. Crucially, in common with other large-scale businesses, pharmaceutical firms find themselves ‹invited’ to respond positively to the corporate ‹social’ responsibility (CSR) expectations of their stakeholders. Consequently, individual managers will almost certainly be obliged to engage in some form of stakeholder dialogue and this, in turn, means that they will have to make difficult choices about which practices to adopt. This real-world management predicament runs parallel to an academic interest in CSR stakeholder dialogue theory and models. Accordingly, the approach of this paper is to focus primarily on the academic debate surrounding stakeholder dialogue, by reviewing past attempts to research and theorise the subject, by identifying gaps and weaknesses in the literature, and by proposing a new analytical model. The central aim of the proposed new model is to offer a unified, structured, systematic, and comprehensive approach to CSR decision making whilst simultaneously providing a practical framework for CSR executives who face the challenge of responding in an effective manner to stakeholders. The model outlined here is currently being employed to conduct international comparative empirical research into stakeholder dialogue practices amongst UK and German pharmaceutical firms. In the longer term the intention is to use the model to undertake international comparative research encompassing a broader range of countries and industries.